A comparative method for evaluating the natural uranium isotopes 238U and 234U in waters - de Oliveira Thomazini, Fábio [UNESP]; Cigagna, Cristiano [UNESP]; Bonotto, Daniel Marcos [UNESP] (My University, 2015)
238U is the principal isotope of natural U (99.72% abundance) and is the progenitor of the (4n+2) series of radioelements. The isotope 234U is radiogenic and the decay chain from 238U through 234U proceeds as follows: 238U (4.46 Ga, α) → 234Th (24.1 days, β-) → 234Pa (1.18 min, α) → 234U (248 ka, α) → ... The isotopes 238U and 234U are in secular equilibrium in all minerals and rocks greater than one million years old and that are closed systems for U. The 234U/238U activity ratio (AR) is, therefore, unity in the bulk of such systems. However, rock/soil-water interactions frequently result in AR for dissolved uranium that is greater than unity. The main factors affecting the uranium distribution in natural waters are: the uranium content in the rock matrix, sediments or soils and its leaching capacity; the grade of the water hydraulic confinement in relation to dilution effects by meteoric waters; climatic effects; seasonal variability and evapotranspiration influence; the pH and water oxidation state; the concentrations of carbonate, phosphate, vanadate, fluoride, sulfate, silicate, calcium, potassium and others constituents able to form uraniferous complexes or uranium insoluble minerals; the presence of materials with capacity of adsorbing uranium like organic matter, clays, iron oxi-hydroxides, manganese and titanium. The uranium content in groundwater is greatly variable, depending of the lithology and/or proximity of the deposits of this element, where, in many geological contexts values >4μg.L-1 have been considered anomalous. Alongside its economic importance, uranium in the hydrological compartment also should be carefully investigated due to its radiological implication as a consequence of its great mobility in the waters and accentuated potential to cause biological damage. The human organism contains an average of 90μg of U that has been incorporated through the normal water and food ingestion and breathed air, approximately 66% in the skeleton, 16% in the liver, 8% in the kidneys and 10% in other tissues. Most of the U reaching the organism (circa 95%) is absorbed. The provisional guideline value for uranium in drinking water is 30 μgL-1 based on its chemical toxicity for the kidney. Both uranium isotopes 238U and 234U emit alpha particles, requiring adequate techniques for their characterization. This chapter describes methods utilizing different ion exchange resins for performing their extraction from waters as well their use in the analyses of different groundwater samples.